O świadomości genologicznej Józefa Piłsudskiego (rekonesans) - Bryła , Władysława (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
The article describes Józef Piłsudski’s texts on various types of speech. The bibliography of Piłudski’s works includes over thirty types of speech, which speaks to his linguistic agility. Our outline includes the analysis of four selected types of texts: aphorism, diatribe, denunciation and feuilleton written in various times in the course of his life. All of them were persuasive in nature and were written using a highly emotional language.